2014
DOI: 10.1371/journal.pone.0101022
|View full text |Cite
|
Sign up to set email alerts
|

Development to Term of Cloned Cattle Derived from Donor Cells Treated with Valproic Acid

Abstract: Cloning of mammals by somatic cell nuclear transfer (SCNT) is still plagued by low efficiency. The epigenetic modifications established during cellular differentiation are a major factor determining this low efficiency as they act as epigenetic barriers restricting reprogramming of somatic nuclei. In this regard, most factors that promote chromatin decondensation, including histone deacetylase inhibitors (HDACis), have been found to increase nuclear reprogramming efficiency, making their use common to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…After many years of research, no dramatic increase in cloning efficiency has been observed, with the rate of survival of cloned embryos still varying from 0 to 12% (De Bem et al, 2011;Sangalli et al, 2014;Gerger et al, 2016). Some improvements in survival rate can be expected by using specific and intensive management and clinical procedures during the perinatal and postnatal periods (Meirelles et al, 2010).…”
Section: Cloningmentioning
confidence: 99%
“…After many years of research, no dramatic increase in cloning efficiency has been observed, with the rate of survival of cloned embryos still varying from 0 to 12% (De Bem et al, 2011;Sangalli et al, 2014;Gerger et al, 2016). Some improvements in survival rate can be expected by using specific and intensive management and clinical procedures during the perinatal and postnatal periods (Meirelles et al, 2010).…”
Section: Cloningmentioning
confidence: 99%
“…Moreover, the use of the artificial modifiers of epigenomically conditioned gene expression leads to the inhibition of both chromatin condensation and transcriptional silencing of the genomic DNA of cultured somatic cells that are applied as a source of donor nuclei for the reconstruction of enucleated oocytes and subsequent generation of cloned embryos. The members of these epigenetic modifiers are 5-aza-2′-deoxycytidine (5-aza-dC) [ 37 , 39 41 ], S -adenosylhomocysteine (SAH) [ 42 ], trichostatin A (TSA) [ 6 , 19 , 36 , 38 , 43 ], valproic acid/sodium valproate (VPA/SV) [ 44 , 45 ], 6-(1,3-dioxo-1 H ,3 H -benzo[de]isoquinolin-2-yl)-hexanoic acid hydroxyamide called scriptaid [ 46 49 ], sodium butyrate (NaBu) [ 50 , 51 ], m -carboxycinnamic acid bis hydroxamide (CBHA) [ 30 , 52 ], and oxamflatin [ 29 , 53 ]. The onset of chromatin decondensation and gene transcriptional activity is evoked by nonspecific/nonselective blocking of the activity of either DNMTs by 5-aza-dC and SAH [ 41 , 42 ] or HDACs by the TSA, VPA, scriptaid, NaBu, CBHA, and oxamflatin [ 30 , 36 , 44 , 48 , 51 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have showed that the developmental defects of cloned embryos fail to eliminate epigeneticspecific markers completely and establish the related gamete markers themselves (Kishigami et al, 2006;Latham, 2005;Rideout et al, 2001;Shi et al, 2003). Moreover, many studies also found that an abnormal epigenetic modification might result in the developmental failure of SCNT embryos, such as abnormal histone acetylation and DNA methylation in reprogramming (Bohrer et al, 2014;Enright et al, 2005;Jafarpour et al, 2011;Sangalli et al, 2014). Histone acetylation is a part of epigenetic modification (Grunstein, 1997;Turner, 2002) and is related to transcriptional activation by regulating the chromosome structure.…”
Section: Discussionmentioning
confidence: 99%